METODE KRITIK HADIS MUSALSAL MUHAMMAD YASIN AL-FADANI: Studi Analisis Komentar Hadis Musalsalat - Wisnuaji, Angger; Dadah, Dadah (DIRAYAH : Jurnal Ilmu Hadis, 2022)
This study discusses the method of criticism of musalal hadith carried out by Muhammad Yasin al-Fadani who is one of the scholars of hadith from Indonesia who received the title of World Musnid. This study explains how to understand the rules of criticism carried out by al-Fadani From his comments on musalal hadith narrated by him in his two books Ithaf al-Ikhwan and al-U'jalah, as for the method he uses in commenting on musalsal hadith, first, he does jarh or weakens hadith based on as-Sakhowi opinion. Second, he expressed his opinion on the hadith after expressing the opinion of the previous scholars. Third, he always collects various routes first, then formulates laws. Fourth, he rarely judged hadith directly, but judged it through the cues he gave from the laws of previous scholars.